Transnational competence frameworks and national curriculum-making: the case of Sweden. Issue 1 (2nd January 2021) - Nordin, Andreas; Sundberg, Daniel
ABSTRACT: Competence-based approaches (CBAs) in education have become an internationally important educational policy concept in recent decades. However, a substantial body of research has suggested that in order to understand and explain the evolution of CBAs, there is a need to analyse curriculum-making as a complex and multi-layered practice. To contribute to this research field, this paper makes use of Vivien Schmidt's concept of discursive-institutionalism (DI), which focuses on ideas and discourse. First, we compare ideas of competences as expressed in four influential CBA frameworks, and second, we exemplify how these ideas, with special reference to the Organisation for Economic Co-operation and Development, have been translated when re-contextualised within Swedish curriculum policy-making. The results show that when re-contextualised within national borders, transnational ideas of competences are reconfigured. In the case of Sweden, this process has led to a national interpretation of CBAs, discussed in this paper as 'hybrid competences.'